Chemical Characteristics of cull Ongole Beef Sausage with Substitution of Tapioca and Soy Bean Flour - Sulmiyati, Sulmiyati; Mbela, Gaudensia; Sabtu, Bastari; Malelak, Gemini E. M. (Journal of Tropical Animal Science and Technology, 2024)
The research aims to analyze the effect of adding tapioca and soybean flour (Glycine max) with different levels on the chemical characteristics of cull Ongole beef sausages. This research used the experiment method with Completely Randomized Design (CRD) method which consisted of five treatments and three replications so that there were 15 experimental units. The treatment consisted of tapioca with soybean flour formula (P0=20%:0%, P1=15%:5%, P2= 10%:10%, P3=5%:15%, P4= 0%:20%). The variables measured are water content, protein content, fat content, and cholesterol content. The results of the research showed that the substitution of soybean flour with tapioca flour had a very significant effect (P<0.01) on water, protein, fat and cholesterol levels. In conclusion, soybean flour substitution had an influence on the chemical quality of beef sausages, at formula levels, soybean flour substitution resulted in a decrease in water content and fat content and an increase in protein content, as well as a decrease in cholesterol levels in line with the increase in soybean flour substitution.